Understanding and Summarizing Answers in Community-Based Question Answering Services - Liu, Yuanjie; Li, Shasha; Cao, Yunbo; Lin, Chin-Yew; Han, Dingyi; Yu, Yong (COLING 2008, Manchester, UK, 2008)
Community-based question answering (cQA) services have accumulated millions of questions and their answers over time. In the process of accumulation, cQA ser-vices assume that questions always have unique best answers. However, with an in-depth analysis of questions and answers on cQA services, we find that the assump-tion cannot be true. According to the anal-ysis, at least 78% of the cQA best answers are reusable when similar questions are asked again, but no more than 48% of them are indeed the unique best answers. We conduct the analysis by proposing taxonomies for cQA questions and an-swers. To better reuse the cQA content, we also propose applying automatic sum-marization techniques to summarize an-swers. Our results show that question-type oriented summarization techniques can improve cQA answer quality significantly.